Bridging indigenous art and sustainability: transformative museum learning in management education - Yang, Charlie (Humanistic Management Journal, 2025)
Keywords: Bridging (networking); Computer science; Ecology; Environmental ethics; Indigenous; Pedagogy; Philosophy; Sociology; Sustainability; Transformative learning; dept.mgt

Mindfulness meditation and art appreciation as meaning-making practices - Yang, Charlie (Academy of Management, 2016)
Mindfulness has recently gained significant attention and momentum in academia and popular culture. There is, however, a paucity of literature on how students make sense of contemplative practices. This paper proposes that mindfulness meditation is not merely a useful tool for stress reduction, but also a metacognitive meaning-making practice.
Keywords: Art appreciations; Contemplative practice; Meaning makings; Metacognitives; Popular cultures; Stress reduction; dept.mgt

Towards an integrated understanding of art, spirituality, and well-being - Yang, Charlie (Journal of Management, Spirituality & Religion, 2023)
Keywords: dept.mgt; peer-reviewed

Museum experiences as innovative pedagogy in contemplative management education for sustainability - Yang, Charlie; Ivanova, Ekaterina; Ivanova, María (Academy of Management Proceedings, 2025)
Keywords: Contemplation; Curriculum; Environmental education; Experiential learning; Mindset; Reflective practice; Sustainability; Sustainable business; Visual arts education; dept.mgt

Making sense of mindfulness in management education - Yang, Charlie (Developing a Sustainability Mindset in Management Education, 2018)
Keywords: dept.mgt

Using contemplative photography in transformative sustainability management education: Pedagogical applications in the united states, russia and germany - Yang, Charlie; Ivanova, Ekaterina; Hufnagel, Julia (The International Journal of Management Education, 2021)
Developing a sustainability mindset requires a transdisciplinary approach to business education that integrates a rational-analytic mode of thinking and an emotive-holistic understanding of the human mind. In order to cultivate the sustainability mindset of business students, we have designed a contemplative art-based project involving the creation of an electronic portfolio which consists of a student's digital photographs. We have integrated it into our teaching of management courses in the United States, Russia, and Germany, respectively. The project aims to enable business students to become more visually attentive and environmentally conscious, so that they will pay close attention to the process of building more sustainable relationships within their natural and social environments. From the interpretative phenomenological perspective, we have analyzed the students' e-portfolios in order to understand how business students make sense of environmental and human sustainability. While envisioning more transformative sustainability management education, we have also discussed the pedagogical implications of making the e-portfolios for enhancing the students' understanding of the sustainability mindset. © 2021 Elsevier Ltd
Keywords: dept.mgt; peer-reviewed

Framing the future: how museums shape sustainability mindsets in business education - Yang, Charlie; Ivanova, Ekaterina; Ivanova, Maria (The Power of Arts-Based Pedagogies: Transforming Mindsets to Shape Our Future, 2026)
Recent research proposes that arts-integrated teaching approaches in business education can nurture students' aesthetic sensitivity and emotional capacities, such as self-awareness and empathy. In this chapter, we examine the pedagogical possibility of art appreciation in art museums as a consciousness-raising practice, especially for the sake of cultivating business students' environmental awareness in two different contexts. We have analyzed American and Russian students' reflective essays based on their museum visits in order to explore how business students make sense of their aesthetic experiences and how art appreciation helps them to develop their sustainability mindset in a creative learning space. Through attentive viewing of the works of art, students have learned some key insights from their aesthetic appreciation at art museums. These insights not only facilitated honing their emotional skills, but also deepened their environmental awareness and heightened their sense of personal empowerment to act upon these newly acquired insights and values ensuing from art appreciation. After identifying six key themes extracted from both groups of students' essays based on their museum learning, we further discuss the pedagogical implications of contemplative art appreciation in museums as a means of contributing to more innovative and sustainable management education. © 2026 selection and editorial matter, Ekaterina Ivanova, Isabel Rimanoczy and Divya Singhal; individual chapters, the contributors.
Keywords: dept.mgt

Arts-based pedagogy in management education: personal reflections - Yang, Charlie; Ivanova, Ekaterina; Ivanova, Maria (Honing Self-Awareness of Faculty and Future Business Leaders: Emotions Connected with Teaching and Learning, 2023)
Historically business education has put greater emphasis on rational analysis and the acquisition of instrumental and technical knowledge, while paying relatively scant attention to developing business students’ soft skills such as self- and social awareness and emotional intelligence through contemplative learning. In light of the growing need for more open and diverse ways of knowing that are more holistic, emotional, and aesthetic in management education, the authors present a 2 × 2 framework of arts-based pedagogy which helps organize various arts-based practices currently used in management education. The authors also share their personal reflections on using artful practices, specifically focussing on two individual-level experiential learning activities (i.e. museum visits and e-portfolio projects) and one group-based participatory art project. The authors further discuss why creative thinking and innovative arts-based practices can open up a new possibility for filling the gaps in current management education, especially in regard to developing students’ self- and social awareness and environmental consciousness in a more creative manner.
Keywords: Arts-based pedagogy; Digital photography; Electronic portfolio (e-portfolio); Museum learning; Participatory art; Socially engaged art; dept.mgt